2019
DOI: 10.1016/j.fertnstert.2018.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Perceived infertility and contraceptive use in the female, reproductive-age cancer survivor

Abstract: Objective: To estimate the association between perceived fertility potential and contraception use and to characterize factors important in contraceptive decision making in reproductive-age, female cancer survivors. Design: Cross-sectional study. Setting: Participants were from two state cancer registries, physician referrals, and cancer survivor advocacy groups in the United States. Patient(s): A total of 483 female survivors aged 18-40 years. Intervention(s): Online questionnaire. Main Outcome Measure(s): Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…A systemic review by Schmidt et al provides an overview of patient-reported concerns regarding post-cancer parenthood, which contribute to decisions to live a childfree life (3). Among the most common concerns were those that involved the child's health, specifically that the child may be at higher risk for cancer themselves or may have poorer health if born after cancer (30)(31). The validity of these medical concerns varies by prior cancer treatment exposures, but most data are reassuring that children born of cancer survivors are not at higher risk of birth defects, chromosomal abnormalities, or childhood cancer (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…A systemic review by Schmidt et al provides an overview of patient-reported concerns regarding post-cancer parenthood, which contribute to decisions to live a childfree life (3). Among the most common concerns were those that involved the child's health, specifically that the child may be at higher risk for cancer themselves or may have poorer health if born after cancer (30)(31). The validity of these medical concerns varies by prior cancer treatment exposures, but most data are reassuring that children born of cancer survivors are not at higher risk of birth defects, chromosomal abnormalities, or childhood cancer (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the literature, data suggest that they are less likely to receive adequate contraception counselling, with rates up to 56% of survivors reporting no family planning counselling at all (Castro-Sanchez et al, 2018). Additionally, they are less likely to be satisfied and compliant with the prescribed method (Blouet et al, 2019) and more likely to wrongly assume they are infertile and to face unwanted pregnancies (Medica et al, 2018;Hadnott et al, 2019). Information on contraception during chemotherapy, along with information on fertility preservation, is part of our pre-therapy counselling.…”
Section: Discussionmentioning
confidence: 99%
“…31e33 Of those survivors with a history of chemotherapy, having the perception of infertility is predictive of contraception nonuse, even without clinical evidence of infertility. 34 As such, discussions about fertility preservation provide an ideal opportunity to provide education about the continued need for contraception.…”
Section: Discussionmentioning
confidence: 99%